2019
DOI: 10.1371/journal.pone.0224690
|View full text |Cite
|
Sign up to set email alerts
|

Serum uromodulin is associated with the severity of clinicopathological findings in ANCA-associated glomerulonephritis

Abstract: BackgroundUromodulin (UMOD), also known as Tamm-Horsfall protein, is a kidney-specific protein expressed by epithelial cells lining the thick ascending limb of the loop of Henle. In the current study, we aimed to clarify the clinical significance of UMOD in ANCA-associated glomerulonephritis (AAG).Materials and methodsSixty-one biopsy-proven AAG patients were included in this study. UMOD was measured using ELISA. The relationships between serum UMOD (sUMOD) levels and various clinicopathological findings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…For example, the top 10 specific genes of kidney are UMOD, SLC22A8, SLC22A12, SLC12A1, SLC22A11, AQP2, SLC12A3, NPHS2, KCNJ1, and SLC22A2. As previous studies reported, uromodulin (UMOD) is a kidney-specific protein ( Tachibana et al, 2019 ) expressed by epithelial cells lining the thick ascending limb of the loop of Henle, the accumulation of mutated UMOD in endoplasmic reticulum can lead to renal injury ( Johnson et al, 2017 ; Trudu et al, 2017 ). In addtion, recent literature also demonstrated that mutation of aquaporin 2 (AQP2) is able to cause nephrogenic diabetes insipidus since AQP2 is responsible for the water reabsorption by kidney collecting duct cells ( Saglar Ozer et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the top 10 specific genes of kidney are UMOD, SLC22A8, SLC22A12, SLC12A1, SLC22A11, AQP2, SLC12A3, NPHS2, KCNJ1, and SLC22A2. As previous studies reported, uromodulin (UMOD) is a kidney-specific protein ( Tachibana et al, 2019 ) expressed by epithelial cells lining the thick ascending limb of the loop of Henle, the accumulation of mutated UMOD in endoplasmic reticulum can lead to renal injury ( Johnson et al, 2017 ; Trudu et al, 2017 ). In addtion, recent literature also demonstrated that mutation of aquaporin 2 (AQP2) is able to cause nephrogenic diabetes insipidus since AQP2 is responsible for the water reabsorption by kidney collecting duct cells ( Saglar Ozer et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tamm‐Horsfall protein, or uromodulin, has been the main protein biomarker to date associated with the TALH (El‐Achkar et al, 2013 ; Wen & Parikh, 2021 ). Previous work has shown a negative correlation between serum uromodulin and AKI in conditions like ANCA‐associated vasculitis (Tachibana et al, 2019 ) and ischemia–reperfusion injury (IRI; El‐Achkar et al, 2013 ), and between urine uromodulin and AKI in diabetes (Chakraborty et al, 2004 ) and patients undergoing cardiac surgery (Zhang et al, 2022 ). Osteopontin, a bone phosphoprotein, is produced predominantly in the TALH but also in the distal convoluted tubule.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several studies have reported direct correlations between serum/plasma UMOD levels and kidney function. 89,[346][347][348] Because serum UMOD often correlates significantly with albuminuria, which is itself a strong predictor of CKD progression, UMOD may also play an important role in the prediction of CKD progression. 349 One prospective study showed that low serum UMOD concentrations in CKD patients was associated with an increased risk of ESRD, independent of the traditional risk factors for progression of CKD.…”
Section: Uromodulinmentioning
confidence: 99%